2022
DOI: 10.1136/bmjopen-2021-060089
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and associated factors of frailty among community dwelling older adults in Northwest China: a cross-sectional study

Abstract: ObjectivesTo investigate the prevalence of the comprehensive frailty and its associated factors among community dwelling older adults.DesignA cross-sectional study.SettingSix community healthcare centres in Xi’an City, Northwest China.ParticipantsA total of 2647 community dwelling older adults completed the study between March and August 2021.Primary and secondary outcome measuresThe primary outcome was the prevalence of frailty, measured with the Comprehensive Frailty Assessment Instrument. The secondary outc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 52 publications
2
1
0
Order By: Relevance
“…The nutritional status was a significant predictive factor of frailty since a lower nutritional status increased the risk of frailty. This finding is similar to previous studies with older adult study populations other than FCs, such as community-dwelling older people [16,[34][35][36]. In addition, previous studies have shown that many FCs are malnourished or at risk of malnutrition [6,37,38].…”
Section: Discussionsupporting
confidence: 91%
“…The nutritional status was a significant predictive factor of frailty since a lower nutritional status increased the risk of frailty. This finding is similar to previous studies with older adult study populations other than FCs, such as community-dwelling older people [16,[34][35][36]. In addition, previous studies have shown that many FCs are malnourished or at risk of malnutrition [6,37,38].…”
Section: Discussionsupporting
confidence: 91%
“…Furthermore, it has been observed that community-dwelling older adults who have attained a university education or higher typically exhibit a reduced degree of frailty. This observation is in alignment with the findings of prior research studies [34,71]. An individual's level of education is intricately linked to their health literacy, coping mechanisms, and the propensity to adhere to healthy lifestyle practices.…”
Section: Socio-demographic Factors Associated With Frailty In Nursing...supporting
confidence: 86%
“…It is noteworthy that three studies [31,47,62] did not make a distinction between male and female participants. Of the entire corpus of studies, 20 [25][26][27]30,[32][33][34]37,41,45,[47][48][49][50]53,57,58,61,62] adopted a cross-sectional design, whereas the remaining 18 [29,31,35,36,[38][39][40][42][43][44]46,51,52,[54][55][56]59,60] constituted cohort studies. The detailed characteristics of the 38 studies included are systematically presented in Supplemental File S2 (Table S1).…”
Section: Characteristics Of Included Studiesmentioning
confidence: 99%